Enhanced Electrocatalysis via 3D Graphene Aerogel Engineered with a Silver Nanowire Network for Ultrahigh‐Rate Zinc–Air Batteries. (24th March 2017) - Hu, Shang; Han, Ting; Lin, Chao; Xiang, Weikai; Zhao, Yonghui; Gao, Peng; Du, Fuping; Li, Xiaopeng; Sun, Yuhan
Abstract : 3D graphene aerogel (GA) integrated with active metal or its derivatives has emerged as a novel class of multifunctional constructs with range of potential applications. However, GA fabricated by self‐assembly in the liquid phase still suffers from low conductivity and poor knowledge related to spatial active phase distribution and 3D structure. To address these issues, a facile approach involving in situ integration of 1D silver nanowire (AgNW) during gelation of graphene oxide flakes is presented. AgNWs prevent the restacking of graphene sheets and act as an efficient electron highway and Ag source for deposition of ultrasmall Ag nanocrystals (AgNCs). When applied as the cathodic electrocatalyst in a zinc–air battery, the 3D GA integrated with 0D AgNCs and 1D AgNWs permit ultrahigh discharge rates of up to 300 mA cm −2 . Moreover, for the first time, with the help of phase‐contrast X‐ray computed microtomography, the interconnected porous network of millimeter‐sized GA and a full‐field view of the macrodistribution of Ag is delivered, offering the vitally complementary macroscopic structure information, which has been missing in previous reports. Abstract : X‐ray computed microtomography (X‐ray μCT) reveals the macrodistribution of active phase (i.e., Ag) and supermacroporous structure in the self‐assembled graphene aerogel for the first time. The interconnected 3D Ag network is the key to achieve high oxygen reduction reaction activity and utrahigh rate performance in Zn–air batteries.